Teachers’ Experience in Curriculum Implementation: An Investigation on English Language Teaching in Vocational Colleges in Malaysia (Sains Humanika, 2017)
This qualitative research aimed to explore teachers’ experience in the implementation of the new English language curriculum in Malaysian vocational colleges. The research’s focus is on English as a Second Language (ESL) teachers’ perceptions on the new English language curriculum and its implementation, ESL teachers’ strategies in implementing the new English language curriculum, and the problems and challenges that they face in implementing the new English language curriculum. A full qualitative research paradigm was employed using a phenomenology design, where 6 ESL teachers from Negeri Sembilan participated to share their insights on the research topic. The research used purposive sampling method, and the participants were selected based on research location. The research instrument used to collect the data was a semi-structured interview administered via Facebook video call and recorded with Callnote application software. This approach was chosen for its feasibility and cost-saving nature. Research findings show that ESL teachers are receptive of the curriculum change and most of them understand the new curriculum well. They have positive feelings towards it despite acknowledging negative curriculum aspects, having curriculum concerns and dealing with problems and challenges. Teachers recommended for proper training and support in order to improve the teaching and learning process in ESL classroom. The implications of the research findings have been outlined and highlighted, followed by several suggestions for the stakeholders involved, including ESL teachers, policymakers, training division, and vocational college administrators.
Keywords: ESL teacher; English Language curriculum; curriculum implementation; Malaysian vocational college.